Primary challenges for employee health and wellbeing - van Dick, Rolf (Frontiers in Organizational Psychology, 2023)
In this short review, I am developing a list of the grand challenges for employee health and well-being utilizing three different sources: Textbook knowledge, expert opinions, and artificial intelligence. Doing so reveals three main topics, namely (1) Stress and its effects on mental and physical health; (2) uncertainty coming with constant and partly dramatic organizational and societal change; and (3) work-life balance and detachment. This list of challenges may be useful for researchers designing new theory and research and for practicing managers.